Internationalisation of Teaching and Learning through Blended Mobility: Potentials of Joint International Blended Courses and Challenges in Their Implementation - René Perfölz; Asun López-Varela (MDPI AG, 2022)
Blended Mobility formats such as joint international blended courses have the potential to enable more students at universities and other HEIs to gain international experiences in the course of their studies. They enhance transnational cooperation in the European Higher Education Area by building bridges at the crossroads of education, research, innovation, serving society and economy. In this article, the authors reflect on their experiences in the conception, planning, organisation and implementation of a joint international blended course between Freie Universität Berlin and Universidad Complutense de Madrid in the field of sustainable development in the summer semester of 2022. The course was offered within the framework of the Erasmus+ KA3 project "Online Pedagogical Resources for European Universities" (OpenU project).